PENGARUH KESEHATAN BANK TERHADAP HARGA SAHAM DENGAN PROFITABILITAS SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN PERBANKAN TAHUN 2017-2021 - Ario Guntara; Nur Aida Arifah Tara; Laila Wardani (Master of Management, Mataram University, 2023)
This study aims to examine and analyze the effect of bank soundness on stock price with profitability as an intervening variable in the banking companies in 2017-2021. The type of this research is an associative research with sample survey as data collection methods. The population in this study was 46 banking companies that listed on the IDX in 2017-2021 using a purposive sampling methods, which is 26 companies are obtained as a sample research. The data analysis technique used is Path Analysis. Based on the test and data analysis result shows that CAR is negative and insignificant on profitability, NPL is negative and significant on profitability, NPM is positive and insignificant on profitability, LFR is positive and significant on profitability, CAR is negative and insignificant on stock price, NPL and LFR is negative and insignificant on stock price, NPM is positive and insignificant on stock price, profitability is positive and significant on stock price, profitability unable to mediates the effect of CAR and NPL on stock price, and profitability mediates the effect of NPM and LFR on stock price.